Revisiting Islamic Leadership: Clarifying Theoretical Issues - Randhy Nugroho; Nadia Rachma Pratiwi (Universitas Gadjah Mada, 2023)
Introduction/Main Objectives: Theory of Islamic Leadership emerged as a form of counter-hegemony to western perspectives of leadership. Background Problems: However, the lack of clarity in Islamic leadership theories, has put Islamic leadership in a dangerous ambiguity due to its overlapping nature to other contemporary constructs. Novelty: This study contributed on the mapping of the Islamic leadership on the world of leadership studies, to some extent the Islamic leadership has significant impact of the well-being followers. Research Methods: This research aims to clarify such issue by using employing integrative review as a method to critically examine the academic interpretation of Islamic Leadership and provide distinguishing features of Islamic Leadership. Finding/Results: This paper argue that 4 (four) features are critical to define Islamic leadership concept: first, the requirement of Islamic morality as the primary moral foundation; second, leadership is a requirement for every human being; third, the presence of outward and inward dimension of leadership and last, leadership as a means rather as an end. Conclusion: This paper concludes by discussing limitation and future research agenda to advance Islamic leadership.